Sultan's Law and Islamic Sharia in The Ottoman Empire Court: An Analysis of The Existence of Secular Law - Fatarib, Husnul; Meirison, Meirison; Saharuddin, Desmadi; Bahar, Muchlis; Karimullah, Suud Sarim (Al-Istinbath: Jurnal Hukum Islam, 2023)
This article aims to describe the impact of legal dualism within the Ottoman Empire. After Constantinople was taken over, Sultan Muhammad Al-Fatih instituted a significant policy, including issuing laws and regulations for the benefit of society; then, there was also a dualism system within the Ottoman Empire, which was visible during the reign of Sultan Sulaiman I. During this time, foreign nationals were mainly recruited, and foreign traders began to gain impunity at the peak of power. This then prompted several questions, such as were the sultans free to create the laws they wanted, or was Islamic law still binding on them? Was Sultan's law an innovation from the Ottoman Empire or a legacy from the preceding dynasty in the form of Capitulation? To address those issues, the authors conducted a comparative historical analysis of various types of literature. We used a descriptive qualitative approach to QÄnÅ«n's position, which served as a springboard for foreign intervention in an Empire that was strong but weak in political policies which occasionally strayed outside the corridor of Islamic Sharia which had become customary and national culture. The tolerance separated from the corridors of Islam derailed during the crisis. This became a springboard for legal dualism in a state body with integrity in various dimensions. Keywords: Sultan's Law, Sharia, Judiciary,Â  Ottoman